An Introduction to The Cancer Genome Atlas - Broom, Bradley M.; Akbani, Rehan (Advances in Statistical Bioinformatics, 2013)
IntroductionThe Cancer Genome Atlas (TCGA) is an ambitious undertaking of the National Institutes of Health (NIH), jointly led by the National Cancer Institute (NCI) and the National Human Genome Research Institute (NHGRI), to identify all key genomic changes in the major types and subtypes of cancer. In the following section, we briefly review the history and goals of the TCGA project. Section 2.3 describes how samples are collected and analyzed by the TCGA. Section 2.4 details how data are processed, stored, and made available to qualified researchers. Section 2.5 briefly surveys several widely available tools that can be used to analyze TCGA data. Section 2.6 summarizes the chapter.History and Goals of the TCGA ProjectAt the turn of the century, it was clear (Balmain et al., 2003) that genomic alterations played a key role in cancer development and progression and that understanding these changes would be enormously important for devising improved methods for diagnosing clinically relevant cancer subtypes and for developing novel molecular therapies aimed at a specific cancer subtype. Several successful treatments for targeting cancer cells with specific genomic changes had been developed – for instance, Gleevec for chronic myeloid leukemia and Herceptin for breast cancer. Early experiments to determine the genomic basis of specific cancers had made it clear that the scope of the genomic changes concerned was enormously complex: an individual cancer could involve hundreds or thousands of genomic alterations, and these changes were for the most part specific to the cancer concerned.